2019
DOI: 10.1002/ece3.5581
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐mediated indirect interactions: Moose browsing increases sawfly fecundity through plant‐induced responses

Abstract: Induced responses in plants, initiated by herbivory, create potential for trait‐mediated indirect interactions among herbivores. Responses to an initial herbivore may change a number of plant traits that subsequently alter ecological processes with additional herbivores. Although common, indirect interactions between taxonomically distant herbivores, such as mammals and insects, are less studied than between taxonomically related species (i.e., insect–insect). In terms of mammal–insect interactions, effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
(97 reference statements)
2
12
0
Order By: Relevance
“…The female cocoons were weighed with a microbalance (Mettler Toledo MX5) approximately two to three weeks after collection and prior to adult emergence. We weighed only female cocoons as a proxy for fecundity, because a strong correlation between egg load and cocoon weight has been established (Nordkvist et al ., 2019). To calculate predation mortality, we used the larvae from the predation treatment by summing up the number of predated and parasitized larvae and divided that number by the initial number of larvae in the group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The female cocoons were weighed with a microbalance (Mettler Toledo MX5) approximately two to three weeks after collection and prior to adult emergence. We weighed only female cocoons as a proxy for fecundity, because a strong correlation between egg load and cocoon weight has been established (Nordkvist et al ., 2019). To calculate predation mortality, we used the larvae from the predation treatment by summing up the number of predated and parasitized larvae and divided that number by the initial number of larvae in the group.…”
Section: Methodsmentioning
confidence: 99%
“…For each experimental pine, we collected 20 needles of the previous year from the branch that hosted the sheltered groups after the sawfly larvae had spun cocoons. The collected needles reflect the food quality that the larvae experienced as the response of pine to sawfly defoliation has not been found to induce an immediate or delayed induced response (Niemelä et al ., 1991; Lyytikäinen, 1994; McMillin & Wagner, 1997; Lyytikäinen‐Saarenmaa, 1999; Nordkvist et al ., 2019). The collected needles were immediately folded in aluminium foil and placed in a plastic box containing dry ice to avoid any resin acid degradation.…”
Section: Methodsmentioning
confidence: 99%
“…Sawflies are subjected to predation in their larval stage by various generalists, mainly ants (Olofsson, 1992;Lindstedt et al, 2006;Kaitaniemi et al, 2007) and spiders (Juutinen, 1967;Kaitaniemi et al, 2007). Sawfly performance is commonly related to pine needle nitrogen (Björkman et al, 1991(Björkman et al, , 1997 and diterpene content (Larsson et al, 1986;Björkman et al, 1997), but moose browsing has previously been shown not to influence sawfly bottomup survival (Nordkvist et al, 2019). Predation of sawfly larvae is commonly related to pine needle diterpene content, due to sequestering and related anti-predator behavior by sawfly larvae (Lindstedt et al, 2006;Kollberg et al, 2015), but moose browsing has previously been shown not to affect diterpene content of pine needles (Nordkvist et al, 2019).…”
Section: Study System and Current Knowledgementioning
confidence: 99%
“…d) interference of the companion's non-volatiles (e.g., saponins) with the ingestion of the imbibed phloem (Koul 2008;Ben-Issa et al 2017). e) aerial and below-ground communication between the plant neighbours (host [hospitable] and companion [hostile]) which alters the aphid-embedding context making it more uncertain and/or disturbing (Law and Regnier 1971;Ninkovic et al 2013;Ben-Issa et al 2017;Elhakeem et al 2018;Kalske et al 2019); this can be envisioned to occur in a trait-mediated fashion appertaining to the interaction between the metabolites and the microbiomes of both plants, as the companion plant might lead to quality changes in the shared microhabitat and in the accompanied crop (Wu et al 2016;Ben-Issa et al 2017;Khudr et al 2018;Nordkvist et al 2019).…”
Section: On Shallot Perturbation and Predation As Stressors Of The Aphid Pestmentioning
confidence: 99%